THE INTEGRATION OF MEASURABLE AND NON-MEASURABLE INSTRUMENTS IN QUANTITATIVE DA'WAH RESEARCH: AN INNOVATIVE FRAMEWORK FOR ASSESSING DA'WAH EFFICACY - Surya Eka Priyatna; Nuril Huda; Dina Hermina (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2025)
This article explores the integration of measurement and non-measurement instruments in quantitative research methodology for the evaluation of Islamic da’wah. Recognizing the limitations of using purely quantitative indicators, this study highlights the significance of merging structured numeric tools such as questionnaires with non-measurement approaches like interviews, observations, and digital analytics. Drawing from a synthesis of recent scholarly findings, the study elaborates on methodological, cultural, technological, and ethical challenges. It applies an innovative mixed-method approach that enhances the validity, relevance, and cultural responsiveness of da’wah evaluation models. The findings affirm that integrating these instruments offers a holistic and pragmatic understanding of da’wah effectiveness, especially in measuring cognitive, affective, and behavioral impacts on target audiences. This integration also enables participatory evaluation frameworks, supports data triangulation, and addresses the ethical dilemmas in cross-contextual research. The paper concludes that this integrative approach not only enriches research design but also equips da’wah practitioners with evidence-based strategies that are adaptable to contemporary socio-digital landscapes.